The Influence of Lead Underwriter Reputation and Pooling Allotment on Underpricing Before and After the Implementation of the e-IPO Policy - Arwan, Arwan; Raharja, Surya (Yayasan Riset dan Pengembangan Intelektual, 2024)
The e-IPO method is to consider the allocation of the minimum number of shares to retail investors through a more transparent pooling rationing. The purpose of this study is to analyze the impact of lead underwriter reputation and pooling allotment on the implementation of the new policy of the Financial Services Authority (OJK) in the Indonesian Capital Market, namely the transition from conventional IPOs to e-IPOs. This research method is quantitative using secondary data. The population used is companies that have IPOs on the IDX from 2016 - 2023. The samples used in the study are (a) Companies that have IPOs, registered with the OJK and listed on the IDX. (b) Companies that have IPOs, registered with the OJK and listed on the IDX that have complete data for the period 2016 to 2023. (c) Complete MKBD Lead Underwriter data from Companies that have IPOs and (d) complete variable data required in this study are available. The findings of this study highlight several important points: lead underwriter reputation has a significant negative effect on underpricing, lead underwriter reputation, with MKBD as a proxy, has a significant negative effect on underpricing, IPO costs have no significant effect on underpricing, IPO value has no significant effect on underpricing, assets have a significant positive effect on underpricing, firm age has no significant effect on underpricing, percentage of shares offered has a significant positive effect on underpricing, and pooling rationing has a significant negative effect on underpricing, e-IPO policy has a significant negative effect on underpricing.